Investigations of Qur’anic sciences in the vocabulary of the Qur’an’s words (by Raghib al-Isfahani) (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the worlds, and prayers and peace be upon the best of messengers who was sent as a mercy to the worlds, and upon his pure family and companions. And after:The noblest and noblest of sciences are the sciences of the Noble Qur’an, and the many topics covered under it, especially the reasons for its revelation, its order, its compilation, its writing, its readings, its interpretation, its miraculousness, its abrogate and the abrogated, the Meccan, the civil, the decisive and the allegorical, and so on from the Arabic sciences, and what they represent in terms of knowledge. Tools used by the interpreter in clarifying and clarifying the Qur’anic meaning embodying the Almighty’s saying: (And We revealed to you the Remembrance so that you may make clear to people what was revealed to them and that they may reflect) ().The sciences of the Qur’an are the tools of the defender of the book of God, who defended his protector, as they are means that reveal the documentation of the Qur’anic text in terms of the strength of its meanings, the splendor of its systems, the loftiness of its goals, and its values, in other words, it reveals its miraculousness and greatness (), and various Qur’anic studies appeared throughout the Islamic ages. It dealt with the Qur’anic text in its legislative, doctrinal, miraculous, and linguistic aspects, so it was (a science that made Sharia a foundation, and used the rest of the knowledge as servants, from which it takes its principles, and with it interprets its aspects) ().